Nicholas of Cusa and Islam Polemic and Dialogue in the Late Middle Ages - Christopher Levy, Ian; George-Tvrtković, Rita; Duclow, Donald F. (Studies in Medieval and Reformation Traditions, 2014)
To explore Christian-Muslim relations at the dawn of the modern age, this book examines Nicholas of Cusa's seminal works on the Qur'an and world religions. It also considers Muslim responses to Christianity and other Christian writings on Islam. Readership: Graduate Students and Professors. Church History, Medieval History, Historical Theology, Christian-Muslim Relations